Determination of Bisphenol in Indoor Dust Samples by Liquid Chromatography in Combination with Quadrupole Mass Spectrometry (LC-MS/MS) - Thuy, Le Minh; Lieu, Dang Thi; Nam, Vu Duc; Ngoc, Nguyen Thuy; Anh, Duong Hong; Tri, Tran Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3, 2022)
This study has focused on the development of the method LC-MS/MS to determine 2,2-bis(4-hydroxyphenyl)propane (bisphenol A: BPA) and 4,4’-dihydroxydiphenylmethane (bisphenol F: BPF) in indoor samples by using ultrasonication extraction and solid-phase extraction for preparation. The chromatographic procedure was performed on Kinetex C18 2.1 x 150 mm, 2.6 µm column with mobile phases: 2 mM HCOONH 4 in MeOH and H 2 O:MeOH (90:10,…). The method quantification limits (MQL) of BPA and BPF were 15.0 and 12.0 ng/g, respectively. The mean recoveries were 80.4% for BPA and 93.8% for BPF (RSD<15%). The calibration curve for both BPA and BPF was linear over a concentration range of 1.0 to 500 ng/mL (R 2 ≥ 0.999). Twenty-one samples were collected from private houses, laboratories, drug stores, and plastic recycling factories in Hanoi. BPA and BPF were found in dust samples with frequencies of 85.7 and 100%, respectively. Concentrations of BPA and BPF in dust samples were in the ranges of <MQL–2230 ng/g (mean: 626) and <MQL–149,000 ng/g (mean: 14,700), respectively. Based on the measured concentration, the human exposure to bisphenol via indoor dust ingestion was estimated for various age groups. The estimated exposure dose for people working at plastic recycling factories was the highest level (23.6 ng/kg-bw/day) but lower than the oral reference dose by the EPA and the European Food Safety Authority (50 µg/kg-bw/day).